Answer:
3
Step-by-step explanation:
Rewriting this sentence as an algebraic equation, we get:
3^10 = 3^7 * x^3.
Dividing both sides by 3^7 simplifies the problem:
3^3 = x^3
Here this x corresponds to the 3 in 3^3. Thus, the solution is x = 3.
Using exponent rules and logarithms, the given equation can be simplified and solved to find that x equals 3.
The subject of the question falls into the field of Mathematics, specifically exponent rules, which are used in High School level algebra. In the mathematics problem provided ('3 to the 10th power = 3 to the 7th power times x to the 3rd power'), we need to solve for x using the knowledge of exponents.
First, it's helpful to know that when two expressions with the same base (in this case, 3) are set equal to each other, their exponents must also be equal. Since we know that 3 to the 7th power times x to the 3rd power equals 3 to the 10th power, we can break this down further. This leads to the equation 7 + 3log(x) = 10, where 'log' represents the logarithm.
By simplifying the equation, we get 3log(x) = 10-7, so 3log(x) = 3. Therefore, log(x)=3/3, hence log(x)=1. If we apply anti logarithm on both sides, we'll find that x = 3 to the power of 1, so x = 3. In other words, 3 to the 3rd power will equal3 to the 10th power divided by 3 to the 7th power. Hence, the value of x is 3.
#SPJ3
Answer:
x=45/2
Step-by-step explanation:
4/9=10/x
cross product
9*10=4*x
90=4x
x=90/4
simplify
x=45/2
Answer:
y = 3 and x = 3
Step-by-step explanation:
(11)
The equation of a horizontal line parallel to the x- axis is
y = c
where c is the value of the y- coordinates the line goes through
Here that is 3, thus
y = 3 ← equation of line
(12)
The equation of a vertical line parallel to the y- axis is
x = c
where c is the value of the x- coordinates the line passes through
Here that is 3, thus
x = 3 ← equation of line
Answer:
28, 125
Step-by-step explanation:
Its so easy
1,250 x 4.5 = 5,625
5,625 x 5 = 28,125
Answer:
15/6
Step-by-step explanation:
if ax^2+bc+c=0 is given equation then slope of this equation will be
m=-a/b